Conflitos ambientais entre a arborização urbana, equipamentos públicos e a população em Ponta Grossa-PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
The general objective of this research is to understand the characteristics of conflicts between sidewalk afforestation, public facilities and the population in the urban area of Ponta Grossa-PR, with the following specific objectives: to identify the types of conflicts between sidewalk afforestation and public facilities found in the tree inventory; to demonstrate the relationship between the population and sidewalk afforestation, based on open protocols in the official portals of the City Hall of Ponta Grossa – PMPG; and to analyze the spatial distribution of conflicts between sidewalk afforestation, urban facilities and the population. Inadequate management and planning can favor the presence of socio-environmental conflicts in urban space. These are common situations in which urban afforestation is in conflict with other components of the urban space, such as overhead cabling, sidewalks, traffic and pedestrians. In this context, we seek to understand the types of conflicts between sidewalk afforestation and public facilities, found in the tree inventory. In addition, the population's relationship with urban trees was assessed based on the opening of a process on official portals, online protocol - OXY and the 156 Call Center and a survey of the number of tree falls reported by the 2nd Fire Brigade of the Municipality in 2022, and how the spatial distribution of conflicts was constituted. Three methodological approaches were adopted, the first being the use of an inventory with a sample of 50% of the trees present in 6 neighborhoods in the urban area. The second was the use of the content analysis methodology, and the third was the creation of thematic maps using the Kernel density interpolation technique. A total of 6,752 tree individuals were inventoried on public roads, of which 59.3% presented some type of conflict, the most representative being with electrical stimuli, followed by conflict with another tree, sidewalks, others, walls and signage. The most representative demands were threats of tree pruning and cutting, and the main application of property, personal and urban infrastructure risk. There were 69 occurrences of fallen trees, the highest number in the first half of the year, mainly in the Uvaranas and Contorno neighborhoods. There are conflicting situations in all neighborhoods, which were pointed out both by the technical team that carried out the inventory and by the population, through the disadvantages. Weather events with heavy rains and sales can increase the population's fear of falling trees, and with this, the conflicting situations produce a triple loss, being of a physiological and morphological nature of the plant, to public and private property and to the population itself. Therefore, it is necessary to establish adequate planning of the afforestation through the implementation of planning and management techniques. It is up to the municipality to prepare the Municipal Plan for Urban Afforestation - PMAU, which establishes the guidelines for the consolidation of the harmonious presence between afforestation, public facilities and the population. Finally, this work sought to diagnose the conflicts that exist between urban afforestation, public facilities and the population, with the aim of establishing guidelines for PMAU actions that minimize existing conflicts and enhance the benefits produced by trees in urban spaces.
Keywords: Arborização; Análise de conteúdo; Kernel; Riscos; Queda de árvores; Geografia